Pengaruh Strategi Promosi, Sarana Prasarana, Dan Kemudahan Pembayaran Terhadap Keputusan Pendaftaran Santri Baru Di PP. Darul Ulum Al-Fadholi - Ula, Khofifatul; Farida, Eka; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine and analyze the influence of promotional strategies, infrastructure, and ease of payment on the enrollment decisions of new students at the Darul Ulum Al-Fadholi Islamic Boarding School. This study used a quantitative approach with an explanatory research approach. Data collection was conducted through questionnaires using a saturated sampling method, with the entire population of 85 respondents sampled. The data analysis method used was multiple linear regression to test the simultaneous and partial effects between variables.The results indicate that promotional strategies, infrastructure, and ease of payment jointly influence the enrollment decisions of new students. Partially, all three variables proved to have a significant influence, with promotional strategies being the most dominant factor influencing enrollment decisions. This indicates that the delivery of attractive, easy-to-understand information, and widespread distribution through various media play a significant role in attracting prospective students. Meanwhile, the availability of adequate and comfortable infrastructure fosters trust in the quality of educational services, and a flexible and secure payment system also supports the decision-making process by parents. Keywords: Promotional Strategies, Infrastructure, Ease of Payment, Enrollment Decisions.